What do patients want from their endoscopy experience? The importance of measuring and understanding patient attitudes to their care. Issue 3 (3rd June 2015) - Tierney, M; Bevan, R; Rees, C J; Trebble, T M
Abstract : Understanding and addressing patient attitudes to their care facilitates their engagement and attendance, improves the quality of their experience and the appropriate utilisation of resources. Gastrointestinal endoscopy is a commonly performed medical procedure that can be associated with patient anxiety and apprehension. Measuring patient attitudes to endoscopy can be undertaken through a number of approaches with contrasting benefits and limitations. Methodological validation is necessary for accurate interpretation of results and avoiding bias. Retrospective post-procedure questionnaires measuring satisfaction are easily undertaken but have limited value, particularly in directing service improvements. Patient experience questionnaires indicate areas of poor care but may reflect the clinician's not the patient's perspective. Directly assessing patient priorities and expectations identifies what is important to patients in their healthcare experience (patient-reported value) that can also provide a basis for other forms of evaluation. Published studies of patient attitudes to their endoscopy procedure indicate the importance of ensuring that endoscopists and their staff control patient discomfort, have adequate technical skill and effectively communicate with their patient relating to the procedure and results. Environmental factors, including noise, privacy and the single-sex environment, are considered to have less value. There are contrasting views on patient attitudes to waiting times for the procedure. Implementing patient-centred care in endoscopy requires an understanding of what patients want from their healthcare experience. The results from available studies suggest implications for current practice that relate to the training and practice of the endoscopist and their staff.